Castiel Vitorino Brasileiro: visuals about gender and race - Nunes, Matheusa Moreira; Zanin, Larissa Fabricio (Farol, 2024)
The article presents reflections on the work “Corpo-Flor” by Castiel Vitorino Brasileiro, whose artistic production has been constituted around the debate on gender relations and black raciality, in order to provide new directions for the discussion of the theme. Based on the visualities present in the photographs of the work “Corpo-Flor” and the dialogue with the artist about the work on canvas, we intend to find the ways in which his work has fostered debates on ethnic and gender issues.